Early childhood education professionals' knowledge about prevention, detection and treatment of acute respiratory infections in children - Patrícia Domingos dos Santos; Franciele Cascaes da Silva; Bruna Weber Santos; Camila Isabel Santos Schivinski (Universidade Estadual de Maringá, 2019)
The present study aimed to identify and compare knowledge and practices of early childhood education professionals from three public nursery schools (A, B and C) in the city of Florianópolis/SC relative to prevention, early detection and handling of acute respiratory infections (ARIs) in children aged between zero and six years old. A total of 120 educators answered a questionnaire. The instrument was composed of 15 close- and open-ended questions, five of which were scored. In statistical analyses, the Anova One-Way test revealed no significant differences for knowledge between professionals from the three institutions, with nursery school B having the highest mean score (6.12 ± 0.8), showing fair knowledge about child care. Overall results point to existing gaps concerning the need for guidance on these aspects of a child's health.